Time of flowering and fertilisation of quince varieties - Szabó, T.; Nyéki, J.; Soltész, M.; Szabó, Z.; Tóth, T. (International Journal of Horticultural Science, 1999)
Literature dealing with flowering and fertilisation of quince is scarce. Most controversial and scanty are informations on observations of self- and cross-pollination. According to our observations, differences in blooming time are few (2-3) days only, thus flowering of most varieties is synchronous. The varieties observed are grouped as early, intermediate and late flowering ones. Self fertility of the individual varieties, however, was not assessed unequivocally, therefore it is recommended, by safety reasons, to consider quince actually as a whole to be auto-incompatible. Artificial self-pollination (or rather geitonogamy) as well as cross pollination with other varieties increased substantially fruit set if compared with the results of natural self-pollination (autogamy). According to the fruit set of their open pollinated flowers, varieties have been classified according to fertility as low (below 10 %), medium (between 10 and 20 %) and high (more than 20 %). Cross fertility of varieties is highly variable depending on combination and on season. Contradictory data are probably due to the sensitivity of quince to conditions of search. Better fruit set was coincident with higher number of stout seeds per fruit. Well developed seeds are definitely a prerequisite of larger fruit size.